2017
DOI: 10.1155/2017/1935284
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Characteristics in Patients with Obstructive Sleep Apnea Compared to Healthy Controls

Abstract: Background. The difference in nasal obstruction between OSA patients and healthy individuals is not adequately documented. Our aim was to describe the sinonasal quality of life and nasal function in OSA patients and healthy controls using the sinonasal outcome test-20 (SNOT-20), nasal obstruction visual analog scale (NO-VAS), and peak nasal inspiratory flow (PNIF). Methodology and Principal. Ninety-three OSA patients and 92 controls were included in a case-control study from 2010 to 2015. Results. Mean SNOT-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…It is likely that the included patients are representative of patients with nonsevere OSA, who do not need nasal or pharyngeal surgical corrections, and are referred to Norwegian public and private hospitals. The patients had higher BMI and worse self-reported general health than the Norwegian general population at baseline [ 42 , 43 ], but were comparable to OSA populations in other recent Norwegian studies [ 2 , 44 ]. The mean values for all SF36 domains at baseline were lower than but within one standard deviation from the mean values of the Norwegian general population [ 45 ].…”
Section: Discussionmentioning
confidence: 66%
“…It is likely that the included patients are representative of patients with nonsevere OSA, who do not need nasal or pharyngeal surgical corrections, and are referred to Norwegian public and private hospitals. The patients had higher BMI and worse self-reported general health than the Norwegian general population at baseline [ 42 , 43 ], but were comparable to OSA populations in other recent Norwegian studies [ 2 , 44 ]. The mean values for all SF36 domains at baseline were lower than but within one standard deviation from the mean values of the Norwegian general population [ 45 ].…”
Section: Discussionmentioning
confidence: 66%
“…We compared the results from our patients that reported headache scores between 17 and 25 on the VAS postoperatively with headache scores documented by healthy controls in other studies. We found that healthy people present an average headache score between 16 and 20 on the VAS [32,33], indicating that our patients reached after surgery the same headache level as healthy people.…”
Section: Discussionsupporting
confidence: 59%
“…Repetitive obstructive episodes cause ischemia‐reperfusion injury to the airway, all the while OSA patients have increased systemic inflammatory mediators predisposing the soft tissues to free‐radical development . These same theories have been proposed recently for two small cohort samples finding higher levels of sinonasal complaints in OSA patients, though no study has definitively linked OSA and higher rates of sinusitis. It is worth mentioning that a separate study of our cohort found no difference in sinusitis QOL scores (by Sino‐Nasal Outcome Test) between OSA and non‐OSA patients.…”
Section: Discussionmentioning
confidence: 88%